Menu Close

Find-turn-it-into-non-segma-expression-1-k-1-n-1-1-k-3-2-




Question Number 74573 by Raxreedoroid last updated on 26/Nov/19
Find (turn it into non-segma expression)  1+Σ_(k=1) ^(n−1) (((−1)^k +3)/2)
Find(turnitintononsegmaexpression)1+n1k=1(1)k+32
Commented by mathmax by abdo last updated on 26/Nov/19
let S =1+Σ_(k=1) ^(n−1)  ((3+(−1)^k )/2) =1+(3/2)Σ_(k=1) ^(n−1) (1)+(1/2)Σ_(k=1) ^(n−1) (−1)^k   =1+(3/2)(n−1) +(1/2)(Σ_(k=0) ^(n−1) (−1)^k −1)  =((3n)/2)−(1/2)−(1/2) +(1/2)×((1−(−1)^n )/2) =((3n)/2) −1 +(1/4)(1−(−1)^n )  =((3n)/2)−(3/4) −(((−1)^n )/4)
letS=1+k=1n13+(1)k2=1+32k=1n1(1)+12k=1n1(1)k=1+32(n1)+12(k=0n1(1)k1)=3n21212+12×1(1)n2=3n21+14(1(1)n)=3n234(1)n4
Answered by mind is power last updated on 26/Nov/19
1+Σ_(k=1) ^(n−1) (((−1)^k )/2)+Σ_(k=1) ^(n−1) (3/2)  =1+(((−1))/2).((−1−(−1)^(n−1) )/2)+(3/2)(n−1)  =(((−1)^(n−1) +6n−3)/4)
1+n1k=1(1)k2+n1k=132=1+(1)2.1(1)n12+32(n1)=(1)n1+6n34
Commented by Smail last updated on 26/Nov/19
1−x^n =(1−x)(1+x+x^2 +x^3 +...+x^(n−1) )  ⇔((1−x^n )/(1−x))=1+x+x^2 +...+x^(n−1)   Thus,  Σ_(k=0) ^(n−1) x^k =((1−x^n )/(1−x))
1xn=(1x)(1+x+x2+x3++xn1)1xn1x=1+x+x2++xn1Thus,n1k=0xk=1xn1x
Commented by JDamian last updated on 26/Nov/19
Σ_(k=1) ^(n−1) x^k   is the sum of a geometric progession
n1k=1xkisthesumofageometricprogession
Commented by Raxreedoroid last updated on 26/Nov/19
What the step of expanding Σ_(k=1) ^(n−1) (((−1)^k )/2) called? or how it was done?
Whatthestepofexpandingn1k=1(1)k2called?orhowitwasdone?

Leave a Reply

Your email address will not be published. Required fields are marked *